13th March: 5th Sunday in Lent - MacSwain, Robert (The expository times, 2016)
The article focuses on the sermon to be given on March 13, 2016 and mention on different version of story of Jesus being anointed by a woman whose act is condemned by observers and yet praised by Jesus.